Effect of solidity and airfoil on the performance of vertical axis wind turbine under fluctuating wind conditions. Issue 14 (14th November 2019) - Mantravadi, Bhargav; D., Unnikrishnan; Sriram, Karthik; Mohammad, Akram; Vaitla, Laxman; Velamati, Ratna Kishore
ABSTRACT: Vertical axis wind turbines (VAWTs) are frequently subjected to fluctuating winds in urban environments. In this paper, we studied the effect of airfoil thickness and solidity on the performance of VAWT under fluctuating wind conditions using three-dimensional computational fluid dynamics model with transition SST turbulence model. In this work, NACA 0012, 0015, and 0030 airfoils; two- and three-bladed VAWT are studied. The performance of VAWT is analyzed by varying fluctuation amplitude and frequency. From the results, it is observed that the cycle averaged CP increases with increase in fluctuation amplitude and airfoil thickness. For two-bladed VAWT, the cycle averaged CP reduces with fluctuation amplitude. In contrast, CP increases with fluctuation amplitude for three bladed. In case of fluctuation frequency, all the airfoils exhibited similar trend. The cycle averaged CP increases to a maximum value corresponding to fc = 1 Hz and then decreases with fc . NACA 0030 airfoil curve exhibits relatively higher CP and a uniform performance when compared to that of NACA 0012 and 0015. If the fluctuating wind is characterized by continuous change of frequency, it is desirable to employ the three-bladed VAWT and NACA 0030 air foil for better performance. This work intends to help during the design of VAWT under fluctuating wind conditions.